2010
DOI: 10.1073/pnas.0908441107
|View full text |Cite
|
Sign up to set email alerts
|

High-risk myeloma is associated with global elevation of miRNAs and overexpression of EIF2C2/AGO2

Abstract: MicroRNAs (miRNAs) are noncoding RNAs that regulate global gene expression. miRNAs often act synergistically to repress target genes, and their dysregulation can contribute to the initiation and progression of a variety of cancers. The clinical relationship between global expression of miRNA and mRNA in cancer has not been studied in detail. We used whole-genome microarray analyses of CD138-enriched plasma cells from 52 newly diagnosed cases of multiple myeloma to correlate miRNA expression profiles with a val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
176
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(187 citation statements)
references
References 38 publications
11
176
0
Order By: Relevance
“…The increased expression of Ago2, along with a gain in DNA copy number, was shown to correlate with highrisk myeloma, whereas Ago2 silencing induced by shRNA led to a decreased viability of myeloma cell lines. 20 Interestingly, in our study Ago2 overexpression promoted HCC tumorigenesis and progression, including tumor invasion and distant lung metastasis, which are supported by both in vitro and in vivo experiments. Conversely, Ago2 knockdown induced by RNAi inhibited cell metastasis (Figs.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The increased expression of Ago2, along with a gain in DNA copy number, was shown to correlate with highrisk myeloma, whereas Ago2 silencing induced by shRNA led to a decreased viability of myeloma cell lines. 20 Interestingly, in our study Ago2 overexpression promoted HCC tumorigenesis and progression, including tumor invasion and distant lung metastasis, which are supported by both in vitro and in vivo experiments. Conversely, Ago2 knockdown induced by RNAi inhibited cell metastasis (Figs.…”
Section: Discussionsupporting
confidence: 79%
“…19 Ago2 overexpression was involved in high-risk myeloma by way of elevating global miRNAs. 20 Moreover, the elevated Ago2 expression could raise the possibility that it augments tumorigenic potential in breast cancer by enhancing miRNA activity. 21 It has also been reported that Ago2 knockdown induced apoptosis in myeloid leukemia cells and inhibited siRNA-mediated silencing of transfected oncogenes in HEK-293 cells.…”
mentioning
confidence: 99%
“…A few cases of MM were found to express miR-125b-2, in particular the translocation/cyclin classification #5, involving either the t(14;16)(q32;q23) or t(14;20)(q32;q11) translocations (up to 14-fold upregulation) 50,51 (Table 1). Interestingly, similar to ALL, miR-125b-2 is not overexpressed in MM with trisomy 21.…”
Section: Mir-125b In Multiple Myeloma (Mm)mentioning
confidence: 99%
“…48 Moreover, it is hardly expressed in ALL or myelomas with somatic trisomy 21. 48,50,51 Thus, there is no correlation between the expression of miR-125b and its genomic copy.…”
Section: Mir-125b and Trisomy 21mentioning
confidence: 99%
“…Moreover, several miRNA have been involved in the pathogenesis of multiple myeloma (MM). [1][2][3] In this sense, it has recently been shown that there is a mechanism of p53 regulation through miRNA acting on MDM2 expression; thus, miR-192, 194 and 215 re-expression in myeloma cell lines induced degradation of MDM2 with subsequent p53 up-regulation and cell growth inhibition. 4 In addition, miR-15a and 16 have also been shown to regulate myeloma proliferation by inhibiting AKT and MAP-kinases, and by reducing bone marrow angiogenesis.…”
Section: Introductionmentioning
confidence: 99%